2012
DOI: 10.1177/155892501200700410
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Adding Polypropylene Fibers to Reinforce Lightweight Cement Composites (LWC)

Abstract: The influence of polypropylene fibers has been studied in different proportioning and fiber length to improve the performance characteristics of the lightweight cement composites. Fibers used in two different lengths (6mm and 12mm) and fiber proportions (0.15% and 0.35%) by cement weight in the mixture design. Hardened concrete properties such as: 7-and 28-day compressive strength, splitting tensile strength, flexural strength, water absorption, and shrinkage were evaluated. Fiber addition was seen to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
5
39
0
2
Order By: Relevance
“…In this study, the matrix reinforced with only 54 mm fibers (mix # 2) recorded the highest compressive strength. The findings were similar to the findings by Bagherzadeh et al (2012) who observed longer PP fibers (12 mm) to perform better in compressive strength compared to shorter fibers (6 mm) at 28 days. They also observed the fiber reinforced matrices in their study to perform better in compressive strength compared to the unreinforced ones (Bagherzadeh et al 2012).…”
Section: Compressive Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the matrix reinforced with only 54 mm fibers (mix # 2) recorded the highest compressive strength. The findings were similar to the findings by Bagherzadeh et al (2012) who observed longer PP fibers (12 mm) to perform better in compressive strength compared to shorter fibers (6 mm) at 28 days. They also observed the fiber reinforced matrices in their study to perform better in compressive strength compared to the unreinforced ones (Bagherzadeh et al 2012).…”
Section: Compressive Strengthsupporting
confidence: 93%
“…This opposes particle movement and delays crack formation (Namango, 2006;Tang et al 2006;Elenga et al 2011). Similar to the observations made in this study, Bagherzadeh et al (2012) reported a flexural strength increase in PP fiber reinforced lightweight cement composites compared to the unreinforced composites. They also observed longer PP fibers (12 mm) to perform better in flexural strength compared to shorter fibers (6 mm).…”
Section: Flexural Strengthsupporting
confidence: 89%
“…As shown in Table 6, the increase in acrylic fibre volume fraction generally led to a slight increment in water absorption and reduction of UPV values. This could be attributed to the entrapment of air during mixing, which induced voids in the concrete [55]. Increased water absorption and reduced UPV values of concrete were also observed by other researchers using synthetic PP fibres [33,47,[55][56][57].…”
Section: Water Absorption and Upvmentioning
confidence: 52%
“…For the mixes with 20% GGBS, the use of 0.1% acrylic fibres decreased the shrinkage strain at 60 days by about 6% whereas a slightly higher reduction of about 10% was found for the mix with the addition of 0.2% acrylic fibre and 70% GGBS. The reduction in drying shrinkage with the optimum use of synthetic PP fibres were widely reported from previous studies [3,33,35,55,60]. The reduction in the drying shrinkage with the use of fibres could be explained by the shrinkage restraining effect of fibres by the bridging and stitching of micro-cracks in the concrete.…”
Section: Drying Shrinkagementioning
confidence: 79%
See 1 more Smart Citation